Pengaruh Work Engagement, Pelatihan dan Quality of Work Life (QWL) terhadap Kinerja ASN - Aldi Satria; Zulfadil, Zulfadil; Ahmad Rifqi (Jurnal Ekonomi Manajemen Perbankan, 2025)
This study aims to examine the influence of work engagement, training, and quality of work life on the performance of civil servants (ASN) within the Government of Kuantan Singingi Regency. The population in this study includes all civil servants at the Regional Financial and Asset Management Agency (BPKAD) and the Population and Civil Registration Office (Disdukcapil) of Kuantan Singingi Regency. The sampling technique used is the saturated sampling method, in which all members of the population are included as respondents. This technique is applied due to the relatively small population size, allowing all units to be used as the research sample. The total sample consisted of 56 civil servants, determined using the census formula approach. The analysis method used in this research is Multiple Linear Regression. The hypothesis testing results show that work engagement, training, and quality of work life each have a positive and significant effect on performance, and collectively, they significantly influence employee performance.